ANALISA STRATEGI POSITIONING MEREK: STUDI KASUS INDUSTRI E-COMMERCE DI INDONESIA - Sabilla, Tasya Agustin Elsha; Riorini, Sri Vandayuli; Nisa, Sarah Ade; Zefanya (Business, Economics dan Entrepreneurship, 2024)
This research explores brand positioning strategies in the Indonesian e-commerce industry, employing a quantitative approach and descriptive methods, utilizing SPSS 25 software. Data collection involved surveys and questionnaires, focusing on consumer perceptions of the Shopee, Tokopedia, Bukalapak, Blibli, and Lazada brands. Involving approximately 100 respondents, the study aims to provide in-depth insights into the e-commerce market positioning in Indonesia. The analysis results indicate that ease of use and application design are the most significant factors influencing consumer interest in using e-commerce. Each e-commerce platform underwent validity tests, reliability tests, and discriminant analysis to ensure data reliability and validity. Managerial recommendations include enhancing user experience through the development of user-friendly interfaces and appealing application designs. Periodic evaluations of performance and consumer feedback are highly recommended, utilizing SPSS 25 for sophisticated analysis. This research contributes to understanding consumer preferences and perceptions in the e-commerce industry while formulating relevant recommendations for the management of each e-commerce platform.